Caracteristic of Toponymic Generics in New Brunswick - Rayburn, Alan (Cahiers de géographie du Québec, 1972)
New Brunswick has a large variety of toponymic terminology including ten generics for flowing water, thirty for stationary water, twelve for flat terrain, eighteen for elevated features, and eleven for terrain depressions. Although the variety is impressive certain terms describe vastly different kinds of features, such as gully for both a terrain depression and a narrow coastal water channel. The English language has been the source of ninety of the 132 terms dïscussed in this paper, with the remainder from the French language, except bogan, padou and mocauque, which have been derived from Amerindian sources. Many of the terms occur only in certain areas, such as bogan and gulch in the north part of the province, and heath and thoroughfare in southern New Brunswick. There are also some regional differences in the description of landscape phenomena, examples being meadow near Oromocto and marsh near Sackville identifying similar features.